Bilateral clavicle fractures: A Case Report and Review of Literature's (World Journal of Current Medical and Pharmaceutical Research, 2021)
Clavicle fracture is one of common injuries in young adult and fracture in the middle third is the most common injury cases in clavicle fractures. Although clavicle fractures are often seen, in some circumstances bilateral clavicle fractures can occur due to high-energy impact injury, but this is an extremely rare and seldom reported on. Clavicle fracture is not commonly mentioned as an indication for operative intervention, but in cases of bilateral clavicle fracture surgical intervention managed to limit the duration of functional disability and allowing for an earlier functional recovery.